Performance evaluation of coated carbide and coated cermet tools when turning hardened tool steel - Mohd. Yusof, Noordin (2003)
Hardened steel is widely used in the manufacture of dies, mould and automotive components such as bearings, gears and shafts. The continuous improvements and developments in cutting tool technology coupled with the availability of suitable machine tools have made it possible to machine steel in its hardened form thereby eliminating the heat treatment step, which is required in the conventional approach. Commercially available plastic mould steel, Stavax ESR, which is a premium grade stainless tool steel, has been hardened to (43 ~ 45 HRC) and turned using two commercially available cutting tool inserts with various side cutting edge angles and at various cutting speeds and feed rates. Turning was performed dry and a constant depth of cut was set. The cutting tool inserts used were physical vapor deposition (PVD) multi coated TiCN based cermet grade with TiN inner layer, TiCN intermediate layer and a TiN outer layer (KT 315); and a cobalt enriched, multi coated carbide grade with thick moderate temperature chemical vapor deposition (MTCVD) - TiCN inner layer, an Al2O3 intermediate layer and TiCN and TiN outer layers (KC9110). Tool performance, tool failure modes and wear mechanisms of the said tools were investigated under various cutting conditions. The surface roughness of the turned part and the chip morphology were studied while the cutting forces were also measured. The performance of the cutting tools is described using response surface methodology. The cutting speed and feed are found have an effect on the various responses investigated. Additionally, the side cutting edge angle is also found to provide secondary contribution to the tool life and surface roughness. The use of -5o side cutting edge angle resulted in longest tool and better surface roughness. The mathematical models developed are statistically valid and sound, particularly for Fc. These are verified by the confirmation run experiments and therefore can be used for prediction within the limits of the factors investigated. KC 9110 outperformed KT 315 in terms of tool life for almost all of the cutting conditions tested. The only exception is at a low feed rate of 0.09 mm/rev and a low cutting speed of 100 m/min where the tool life of KT 315 was more than 30 minutes and this was the longest tool life achievable. For KT 315, flank wear and catastrophic failure are the dominant failure modes whereas for KC 9110 it was end clearance wear and flank wear. Flank and end clearance wear probably occur by both abrasive and adhesive wear mechanisms with abrasive wear being the major source of material removal. Catastrophic failure could be associated with a combination of abrasion, adhesion, diffusion, fracture and plastic deformation wear mechanisms. Saw-tooth chips are produced at almost all conditions with the exception of cutting at low cutting speed and feed. White layers are also detected on the chip underside.